EVALUASI DAMPAK PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) TINGKAT SEKOLAH MENENGAH PERTAMA NEGERI (SMP N) DI KECAMATAN BANYUMANIK, KOTA SEMARANG - Indriyana, Dona Lika; Kismartini, Kismartini; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
BOS program is education program from government for poor society to facing the mark-up price of gasoline on 2005. Basically, BOS is non-personal operating fund supplying program from government to access nine years elementary school of national educational system. This research, will observe how far BOS Program that almost ten years works, can give benefit and impact for the targets. Qualitative – descriptive method will used to explain the impact evaluation research by in-depth interview.The results of impact evaluation of School Operational Assistance Program (Program BOS) on junior high school grade in Banyumanik Sub district, Semarang City conclude that the targets give positive effects, despite there are some problems about fund managing. Positive effect not only for the pupils and schools, but also for the parents of pupil in there. Impacts for the pupils are motivation to study, because there isn’t pay to fee and increasing the instruments for study and extracurricular activities. So that, they optimist to steps on next grade after junior high school. Impacts for parents are helping them about school fee, and then parents can fulfilled another requirement that can support their child education. Impacts for the schools are can completely the school requirements for educational activities. The schools applying and managing of the BOS funds following by the BOS rules that regulate about the fee components up to the prohibitions. Over all, BOS program earns good response for decrease the school fees and support school activities. Until now, BOS program can push down the drop out cases in nine years elementary school grade. But, the school has other problems, like the funds was delayed to transfer and limited to accomplish the school requirements.